Pengembangan Media Pembelajaran Interaktif Berbasis Canva pada Pembelajaran Bahasa Arab - Nisa', Khoirun; Muhaimin, Rizal (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This interactive learning media based on Canva is a benchmark for researchers to come up with a creative idea in overcoming the problems that exist at MTs Hasyim Asyári Kedungmegarih. That every time learning a foreign language tends to face various language problems, including the problem of lack of interest in learning. In terms of reading and writing, especially memorizing Arabic vocabulary which is still low. Because of that, they have difficulty understanding the text. The more vocabulary they don't understand, the more difficult it is for them to understand the text. And also the different backgrounds of the students' institutions, some of which are in (SD) and, (MI) are the reasons that make them incompatible in understanding learning when they enter Mts Hasyim Asy'ari Kedungmegarih about understanding how far they know about learning Arabic. This study uses the type of research and development (RnD) Borg and Gall Gall which has been modified by Sugiyono. The results of the study were obtained from the development of interactive learning media based on Canva in Arabic language learning, namely: 1) the procedure for developing interactive learning media based on Canva through the procedures carried out by the researcher in the six stages, this is proven by the results of material validation of 80%, language validation of 80%, media validation of 80%, the results of which 80% are said to be very feasible as learning media, 2) Characteristics of interactive learning media based on Canva through the description of the differences in previous studies and the specifications are stated as media (software/web) Main menu (Cover, Ki Kd, Material, Evaluation) and also from the results of the student questionnaire responses 96.66% really like interactive media learning based on Canva. 3) The feasibility of developing interactive media based on Canva in Arabic language learning, this is proven by the results of the pre-test with a total of 2,842, an average of 54.00. And the results of the post-test amounted to 2,922, an average of 95.00. So that it is proven that there is an increase in the value of 445. 2) With the development of interactive learning media based on Canva, it can increase students' enthusiasm and enthusiasm, so that Arabic language learning is interesting and not boring.